Prophylaxis of post-operative nausea and vomiting in major obstetrics surgeries: a comparative study between palanosetron and neit guam point stimulation - Agarwal, Shaily; Agarwal, Apurva; Gupta, Renu; Gupta, Pranshi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Post-operative nausea and vomiting (PONV) prophylaxis is an important component in providing safe anesthesia in antenatal women. Pharmaceutical interventions like metoclopramide and 5-HT3 antagonists are the current treatment of choice for PONV prophylaxis. However newer drugs are less easily available and more expensive and there is always a concern regarding the effects on fetus. The objective of the study was to evaluate and compare efficacy and safety of antiemetic effects of stimulation of neitguam point stimulation with palonosetron for PONV prevention in obstetric surgeries. Methods: A randomized control trial was done on 150 patients with ASA grade I-II, between ages of 18-45 undergoing obstetric surgery under spinal anesthesia at a tertiary care center. The patients were randomly allocated into two groups using a random sequence. In group I, 76 patients received 75μg palonosetron IV 5 minutes prior to induction. Group II contained 74 patients in which neitguam point stimulation was done by acupressure (wrist band) . All patients were followed till 24 hours post-surgery and incidence of PONV was recorded intra-operative and till 30 minutes, at 2 hours, 6 hours and 24 hours post-surgery. The results were analyzed using SPSS software and chi square test. Results: Both neit guam point stimulation and palanosetron were effective in prevention of PONV (p=0.32). neit guam point stimulation can be considered as effective as palonosetron in prevention of nausea. The cost analysis signifies the advantage of neit guam point stimulation. Conclusions: Neit guam point stimulation is a safe and highly effective method to prevent PONV. It can help in bringing down cost and can be easily made at the small primary healthcare centers and trained midwives.